A marriage of inconvenience - Vastine, Amy (Vastine, Amy. Stop the wedding!, 2021)
"Wedding planner Sophia Reed never imagined she'd meet her perfect man during a bank robbery. Evan Anderson is handsome and funny and makes Sophia believe in love at first sight. There's only one small hitch--he's engaged to someone else, and Sophia is planning his wedding! But Evan's wedding is purely a business arrangement...and true love might just turn this almost-perfect wedding into a beautiful catastrophe!"--